Pengaruh good corporate governance terhadap kinerja perusahaan pada perusahaan transportasi yang terdaftar di Bursa Efek Indonesia tahun 2018 – 2020 - Nugraha, Marchel Azhari; Siregar, Cantika Sari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research focused to analyse the influence of Good Corporate Govarnance (GCG) component Independent Commissioners, Board of Directors and Managerial Ownership on the performance of Transportation companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The phenomenon that occured was the condition of fluctuative transportation sector income in 2018-2020. Data analysis technique is using: (1) Classic Assumption Test, and (2) Hypothesis Testing. The results explain that Independent Commissioners partially have a significantly influence on the company’s perform variable. Board of Directors and Managerial Ownership partially have a significantly negative influence on the company’s perform variable. Simultaneously, the variables of independent commissioners, “board of directors, and managerial ownership as a whole or simultaneously have an influence on the company's perform variables